Peculiarities of electrophoretic deposition and morphology of deposited films in non-aqueous suspensions of Al2O3–Al nanopowder - Elena G. Kalinina; Darya S. Rusakova; Elena Yu. Pikalova (Chimica Techno Acta)
The paper presents the results of a comprehensive study of the electrokinetic properties of non-aqueous suspensions of the Al2O3–Al nanopowder obtained by the method of electric explosion of wires (EEW) with 0.3 wt.% of metallic aluminum in its composition. The dependence of zeta potential on the concentration of the Al2O3–Al suspension is revealed. The nature of long-term changes in zeta potential and pH in suspensions is established. Appearance of bubbles in the deposited coatings due to the interaction of metallic aluminum particles with the liquid suspension medium during electrochemical reactions on the electrodes is defined as the main feature of the electrophoretic deposition (EPD) process in the Al2O3–Al suspensions. The influence of the suspension preparation method on the deposited coatings’ morphology is demonstrated.